High Charge‐Carrier Mobility of 2.5 cm2 V−1 s−1 from a Water‐Borne Colloid of a Polymeric Semiconductor via Smart Surfactant Engineering. (19th August 2015) - Cho, Jangwhan; Cheon, Kwang Hee; Ahn, Hyungju; Park, Kwang Hun; Kwon, Soon‐Ki; Kim, Yun‐Hi; Chung, Dae Sung
<x xml:space="preserve">Abstract</x> Semiconducting polymer nanoparticles dispersed in water are synthesized by a novel method utilizing non‐ionic surfactants. By developing a smart surfactant engineering technique involving a selective post‐removal process of surfactants, an unprecedentedly high mobility of 2.51 cm2 V−1 s−1 from a water‐borne colloid is demonstrated for the first time.